The 1-D bin packing problem optimisation using bees algorithm - Natalia Hartono; Asrul Harun Ismail; Sultan Zeybek; Mario Caterino; Kaiwen Jiang; Murat Sahin; Christine Natalia (Fakultas Teknik Jurusan Teknik Industri Universitas Sultan Ageng Tirtayasa, 2022)
The bin packing problem is a classic combinatorial optimisation problem that is widely used in various applications such as assembly line balancing, scheduling, and time-tabling. Metaheuristic algorithms can provide solutions to these problems faster than exact methods. Bees Algorithm, a metaheuristic algorithm inspired by the foraging activity of bees, is known for its performance in solving optimisation problems. To our best knowledge, this is the first use of the Bees Algorithm to solve a bin packing problem. In this paper, we use the basic Bees Algorithm to demonstrate near-optimal solutions and measure the accuracy of solutions to the one-dimensional bin packing problem. The algorithm procedure and parameter settings are set following the previous research. Benchmark datasets are used in the experiment, and accuracy is measured. The results indicate that the basic Bees Algorithm for bin packing problems and previous research on travelling salesman problems produce similar accuracy results.